Screening the Poor Students for Approval of the Student Loan Fund by Credit Scoring Model: การคัดกรองนักศึกษายากจนให้กู้ยืม กยศ. โดยใช้แบบจำลองการให้คะแนนสินเชื่อ - Plubplueng, Thitima (Journal of Applied Economics and Management Strategy, 2020)
บทคัดย่อ บทความนี้ศึกษาน้ำหนักของหลักเกณฑ์ที่ใช้ในการพิจารณาคัดกรองนักศึกษายากจนให้กู้ยืมจาก กยศ. ของสถาบันการศึกษา โดยใช้แนวคิดทุนมนุษย์ (Human Capital) และการให้คะแนนสินเชื่อบัตรเครดิต (Credit Scoring) ในสถาบันการเงิน โดยใช้การสัมภาษณ์เชิงลึก และแบบสอบถามเป็นเครื่องมือในการรวบรวมข้อมูล กลุ่มตัวอย่างเป็นอาจารย์ที่ปรึกษา จำนวน 225 คน ของมหาวิทยาลัยเทคโนโลยีราชมงคลรัตนโกสินทร์และมหาวิทยาลัยเทคโนโลยีราชมงคลล้านนา โดยใช้การวิเคราะห์ปัจจัย (Factor Analysis) เพื่อหาน้ำหนักของตัวแปรและกำหนดคะแนนเครดิตในแบบจำลองการคัดกรอง พบว่า ความยากจนซึ่งเกิดขึ้นจากเหตุการณ์ที่ไม่คาดคิดมาก่อนของครอบครัวและมีแนวโน้มจะคงอยู่เป็นปัญหาในระยะยาว จะมีน้ำหนักมากกว่าตัวแปรอื่นในการพิจารณาให้กู้ยืม กยศ. ดังนั้นควรนำแนวคิดดังกล่าวไปสร้างนวัตกรรมการคัดกรองโดยใช้เทคโนโลยีสารสนเทศ และปรับปรุงวิธีการคัดกรองและเงื่อนไขการให้ทุนหรือกู้ยืม กยศ. อย่างมีมาตรฐานเดียวกันทั้งมหาวิทยาลัย คำสำคัญ: แบบจำลองการให้คะแนนสินเชื่อ กองทุนกู้ยืมเพื่อการศึกษา (กยศ.) การคัดกรองนักศึกษายากจน ABSTRACT The article aims to study the weight of criteria used for considering screening the poor students for approval of the Student Loan Fund in educational institution. In this regard, the concepts of human capital and credit scoring in financial institutions were used by applying in-depth interviews and a questionnaire. The sample group consisted of 225 advisers at Rajamangala University of Technology Rattanakosin and Rajamangala University of Technology Lanna in Thailand. Factor analysis was applied to find the weight of the variables and to determine the credit score in the screening model. According to the results, poverty caused by unexpected events in the family and tending to remain a long-term problem had more weight than other variables regarding the consideration for approval of a loan of the Student Loan Fund. Therefore, the aforementioned concepts should be applied for creating screening innovation by using information technology. Additionally, the screening method and conditions for approval of the funds or loans of the Student Loan Fund should be improved in order to have the same standard throughout the university. Keywords: Credit Scoring Model, Student Loan Fund, Screening the Poor students